A CASE OF SWOLLEN HANDS AND FEET SYNDROME BUT NOT LEPROSY; A DIAGNOSTIC CHALLENGE - PUSHKAR, PUSHPENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Polyarthritis in leprosy mainly manifests itself in the form of swollen hands and feet syndrome during lepra reactions or insidious-onset chronic symmetrical polyarthritis mimicking rheumatoid arthritis (RA). However, hereby I’m reporting a case in which a patient has swollen hands and feet syndrome but neither he is suffering from leprosy nor RA and asking what’s wrong with me?